The Influence of Learning Management Technology to Student’s Learning Outcome - Taufiq Lilo Adi Sucipto; Agus Efendi; Husni Nadya Hanif; Cucuk Budiyanto (International Journal of Pedagogy and Teacher Education, 2017)
The study examines the influence of learning management systems to the implementation of flipped classroom model in a vocational school in Indonesia. The flipped classroom is a relatively new educational model that inverts students’ time to study on lectures and time spent on homework. Despite studies have been conducted on the model, few addressed the impact of the use of a learning management system to the performance of students involved in such learning model particularly within Indonesian educational systems context. A quasi-experiment approach was applied to an experiment class and another control class. Upon the analysis, the results emphasized previously held research outcomes. The use of Edmodo learning management systems enhances students’ performance in the experiment class, relative to those of the control class.  Except where otherwise noted, content on this site is licensed under a Creative Commons Attribution 4.0 International License.